2021
DOI: 10.18805/ijare.a-5697
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Yield Attribute of Blackgram Genotypes under Different Salinity Stress Conditions

Abstract: Background: Blackgram is one of the important grain legumes in India. Pulses are the important source of protein for the vegetarian people. To meet out the current demand of pulses, there is a crucial need to increase the blackgram production. Mostly this crop is cultivated in marginal lands where the abiotic stresses like drought and salinity are predominant. The area under salinity in India is 6.73 million hectares and in blackgram no variety was identified as suitable for saline areas.Methods: This experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…Due to high level of salinity the sodium salt absorption by the plant may be increased that leads to accumulation in plants. Similar findings were also confirmed in blackgram by Shanthi et al (2021b) and Priyadharshini et al (2019).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Due to high level of salinity the sodium salt absorption by the plant may be increased that leads to accumulation in plants. Similar findings were also confirmed in blackgram by Shanthi et al (2021b) and Priyadharshini et al (2019).…”
Section: Resultssupporting
confidence: 86%
“…Kumar et al (2021) reported that the salinity is a major abiotic stress that significantly affects the plant growth by causing osmotic stress and inducing ionic and nutrient imbalance. The first visible symptom due to salinity is retarded growth (Shanthi et al, 2021b) prolonged salinity the plumule length was reduced. The maximum plumule length after 8 days of germination was recorded by the genotype IPMD 14-10 (18.9 cm) (Table 3) and it was reduced to half in most of the genotypes studied under 8.0 EC level and the length was reduced high at 16.0 EC level.…”
Section: Resultsmentioning
confidence: 99%